Study of long-termed displacements of a tunnel boring machine during its stoppage - Yao, Yanming; Lu, Nan; Yang, Yunming; Cao, Yuxuan; Yu, Hai-Sui (Elsevier, 2019)
This paper studies the long-termed displacement of a tunnel boring machine (TBM) resting on soft clay during its unscheduled stoppage for 100 days. It is based on a real case of tunneling in a coastal city of Ningbo in China. The numerical prediction is carried out by using different soil models in the software PLAXIS, and the prediction is compared with on-site measurement of the displacement. Different factors are considered in the prediction, including soil creeping and the disturbance to the soft clay during the tunneling. The study indicates that the consideration of disturbance is essential to the accurate prediction. While advanced soil models including the soft soil model and soft soil creep model are not able to accurately predict the TBM displacement, the consideration of soil disturbance leads to a very good agreement with the measurement. The accurate prediction of ground settlements also justifies consideration of the disturbance in the study of tunneling. © 2018 Elsevier Ltd